Modulation of Phase Separation by RNA: A Glimpse on N6-Methyladenosine Modification - Su, Yingfeng; Maimaitiyiming, Yasen; Wang, Lingfang; Cheng, Xiaodong; Hsu, Chih-Hung (Frontiers in Cell and Developmental Biology, 2021)
Phase separation is the driving force behind formation of various biomolecular condensates (BioMCs), which sub-compartmentalize certain cellular components in a membraneless manner to orchestrate numerous biological processes. Many BioMCs are composed of proteins and RNAs. While the features and functions of proteins are well studied, less attention was paid to the other essential component RNA. Here, we describe how RNA contributes to the biogenesis, dissolution and properties of BioMCs as a multivalence providing scaffold for proteins/RNA to undergo phase separation. Specifically, we focus on N6-methyladenosine (m6A), the most widely distributed dynamic post-transcriptional modification which would change the charge, conformation as well as RNA-binding proteins (RBPs) anchoring of modified RNA. m6A RNA modulated phase separation is a new perspective to illustrate m6A-mediated various biological processes. We summarize m6A main functions as “beacon” to recruit reader proteins and “structural switcher” to alter RNA-protein and RNA-RNA interactions to modulate phase separation and regulate the related biological processes.